The Sedekah Bumi and Tasyakuran Traditions at Petilasan Genuk Kemiri, Central Java: Strengthening Social Solidarity and Cultural Identity Amid Modernization - Maharani, Ajeng; Illiyyun, Naili Ni’matul (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2025)
This study examines the role of the Sedekah Bumi and Tasyakuran traditions at Petilasan Genuk Kemiri, Kadipaten Pati, Central Java, in promoting social solidarity and preserving cultural identity amid modernization. The main objective of this study is to understand the social and cultural significance of these two traditions, as well as their contribution to strengthening social cohesion and harmony within the community. This study uses a qualitative approach with a descriptive method, involving data collection through observation, interviews with community leaders, traditional leaders, village heads, and the use of related documents and literature as supporting data. The findings indicate that these traditions not only serve as a medium for cultural preservation but also strengthen social bonds and sustain local cultural values. These practices highlight the strong relationship between cultural habits and the historical awareness that continues to be upheld by the community. The Sedekah Bumi and Tasyakuran ceremonies combine spiritual, historical, and social aspects in a sacred ritual, contributing to the strengthening of cultural identity, social relations, and respect for local history. Based on Émile Durkheim’s theory of social solidarity, this study demonstrates how these traditions enhance a sense of unity and social solidarity through cooperation and collective participation. The involvement of community members in contributing labor, material, or prayers illustrates the importance of these traditions in fostering social cohesion and preserving local culture. This study significantly contributes to the development of sociology, particularly in studies on culture, social identity, community cohesion, and social change. Through an in-depth exploration of the Sedekah Bumi and Tasyakuran rituals, this research enriches our understanding of social dynamics in local communities and emphasizes the crucial role of traditions in shaping social solidarity.